Bridging Digital Technology and Local Heritage: An E-Magazine Model for Contextual History Learning in Post-Colonial Urban Spaces - Muhammad Bagas Riyanto; Abdul Rozaq; Dafina Pramuditya; Hany Nurpratiwi; Yudi Pratama (Universitas Negeri Semarang, 2025)
This study develops and evaluates